2018
DOI: 10.1017/etds.2018.122
|View full text |Cite
|
Sign up to set email alerts
|

On geodesic flows with symmetries and closed magnetic geodesics on orbifolds

Abstract: Let Q be a closed manifold admitting a locally-free action of a compact Lie group G. In this paper we study the properties of geodesic flows on Q given by Riemannian metrics which are invariant by such an action. In particular, we will be interested in the existence of geodesics which are closed up to the action of some element in the group G, since they project to closed magnetic geodesics on the quotient orbifold Q/G.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Most notably, Guruprasad and Haefliger [GH06] showed that every nondevelopable compact Riemannian orbifold, i.e. one which cannot be written as a global quotient of a Riemannian manifold M by a proper, cocompact, isometric action of a discrete group G, has a closed geodesic (see also [AS18] for an alternative proof). On the other hand, the assumption that there are no closed geodesics on a developable compact Riemannian orbifold M/G imposes strong restrictions on M , G and its action on M .…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, Guruprasad and Haefliger [GH06] showed that every nondevelopable compact Riemannian orbifold, i.e. one which cannot be written as a global quotient of a Riemannian manifold M by a proper, cocompact, isometric action of a discrete group G, has a closed geodesic (see also [AS18] for an alternative proof). On the other hand, the assumption that there are no closed geodesics on a developable compact Riemannian orbifold M/G imposes strong restrictions on M , G and its action on M .…”
Section: Introductionmentioning
confidence: 99%